Medical Assistance in Dying (MAiD): the opinions of medical trainees in Newfoundland and Labrador. A cross-sectional study. - McCarthy, Robert NG; Seal, Melanie (Canadian Medical Education Journal, 2019)
Background: Medical Assistance in Dying (MAiD) was legalized in Canada in 2016. As future physicians, medical trainees will face decisions regarding MAiD. Although many publications exist internationally, Canadian data is limited in the peer-reviewed literature. The purpose of this study is to determine the opinions of medical trainees in Newfoundland and Labrador regarding MAiD, and the factors that impact these views. Methods: A survey was distributed to all medical trainees at Memorial University (N=570). The survey collected demographic information and opinions regarding MAiD. Respondents were divided into groups based on demographic characteristics, and their responses analyzed using non-parametric statistics. Results: The survey was completed by 124 trainees. Ninety percent of respondents agreed with the legalization of MAiD in Canada and nearly 60% stated they would perform the procedure for their patients. Several factors influenced the opinions of medical trainees, including level of training and religious affiliation. Trainees also favored detachment from the MAiD process. Interpretation: Canadian medical trainees are largely in favor of MAiD, which will likely be requested more frequently in the future. This highlights the importance of emphasizing MAiD within medical curricula, so that trainees are adequately informed and prepared to handle this new aspect of medical care upon joining independent practice.